Comparison of Polypropylene Mesh and Primary Repair in the Treatment of Blunt Testicular Rupture - Tahtali, Ibrahim Nuvit; Halis, Fikret; Yildiz, Turan; Gokce, Ahmet; Ilçe, Zekeriya; Balabay, Mevlana Derya (Urology Journal, 2016)
Purpose: This study aimed to show the applicability of Polypropylene mesh (PM) grafting in blunt testicular ruptures. Materials and Methods: Data of 16 patients treated for testicular rupture following blunt scrotal trauma between March 2007 and April 2015 were analyzed retrospectively. Eight primary repairs and eight PM graftings were performed to repair the tunica albuginea (TA). Postoperatively, patients underwent Doppler ultrasonography at 3 weeks and then at 3, 6, and 12 months, followed by annual scans. The measurement of plasma testosterone levels was performed 12 months after the surgery. Results: The average follow-up time was 24.8 (range 12-48) and 42.8 (range 14-75) months for patients treated with PM grafting and primary repair, respectively. Differences in testicular size between treatment groups were only significant at 12 months postoperatively with the value of 26.5 mL (range 24-28) and 22.8 mL (range 13-27) in patients treated with a PM graft and primary repair, respectively (P = .045). There were no complications for those patients treated with the PM graft. Two patients who underwent primary repair developed testicular atrophy within 1 year postoperatively. Conclusion: PM grafting is a safe alternative to primary closure of a TA defect following blunt testicular trauma.